NATIONALLY ORIENTED PRIORITIES IN TEACHING THE RUSSIAN LANGUAGE AS NATIVE (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-2-176-184The article explains the expediency of nationally oriented teaching of the Russian native language. The article highlights the ideas of the primacy of the native language and cultural traditions of the Russian people as means of development and education of a person. The priorities of nationally oriented teaching of the Russian language are under the analysis. The necessity of a person’s national-cultural identity (rootedness) in the sphere of his native language, way of life, art, nature, and culture of his people is stated. The priority of the axiological approach in teaching the native Russian language is proven.Key words: priority, national identity, image of language, society, value, axiological language technique